Trust in Procurement Interactions - Nicolas Fugger; Elena Katok; Achim Wambach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate the claim that auctions in procurement are detrimental to the buyer- seller relationship, which is expressed by less trust by the buyer and more oppor- tunistic behavior by the supplier after the sourcing. To do so, we compare exper- imentally a standard auction and a buyer-determined auction. It turns out that buyer-determined auctions result in higher prices but enable cooperation between the buyer and the selected supplier. In the buyer-determined auction it can be optimal for the buyer to choose the larger offer. The standard auctions, on the other hand, yield lower prices but reduce cooperation to a minimum. Interest- ingly the degree of trust reflected by a larger number of trades and efficiency in case of trade are significantly higher in the buyer-determined auction. Theoretical reasoning based on other-regarding preferences helps to organize the results.
Keywords: D44; D03; D02; 330